Docência no componente curricular de empreendedorismo: a educação profissional numa perspectiva de aprendizagem empreendedora pela escola remota Joaquim Nabuco no extremo norte do Brasil - SOUZA, Waldeisy Silva de (Instituto Federal do Amapá, 2021)
The theme of this work starts from the importance of the Entrepreneurship Curricular Component of entrepreneurship: Professional Education in an entrepreneurial learning perspective by the Joaquim Nabuco remote school in the extreme north of Brazil, the importance of inserting the discipline in technical courses, having in the context of education entrepreneurial, evidencing the need for an attitude to achieve the expected performance. Entrepreneurship is fundamental to the company's success. Through it, a spontaneously creative center can be created in the organization, generating quick, constant and functional solutions for these organizations. In Brazil it started to develop in the 90's and has a continuous evolution. Students must know and position themselves in relation to the contents aborted by the discipline of entrepreneurship in the classroom with a vision of the future, being able to identify opportunities and transform them into knowledge. Thus, the objective of the work is to identify the importance of entrepreneurial education. To achieve this goal, bibliographic research and an account of the experience in the classroom at Joaquim Nabuco school were carried out.